2019
DOI: 10.1177/1120700019877835
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of total hip arthroplasty in haemodialysis and renal transplant patients: systematic review

Abstract: Background: Chronic renal failure is increasing in prevalence and reported to have deleterious effects on the outcome of total hip arthroplasty (THA). Aim: To investigate the clinical and functional outcomes of THA in patients receiving haemodialysis or who have previously undergone renal transplantation. Methods: Systematic review of the literature using bibliographic databases up to July 2018 to determine the functional outcome, complications and revision rates of THA in patients receiving haemodialysis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…This meta-analysis's main finding is that arthroplasties performed in renal transplant patients have a lower risk of mortality, periprosthetic joint infection, and revision than those performed in dialysis patients. To our knowledge, this is the first meta-analysis on this topic, even though Lieu et al's [27] and Popat et al's [28] systematic reviews have been published. Unlike previous systematic reviews, this review provides a higher level of evidence due to the meta-analysis performed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This meta-analysis's main finding is that arthroplasties performed in renal transplant patients have a lower risk of mortality, periprosthetic joint infection, and revision than those performed in dialysis patients. To our knowledge, this is the first meta-analysis on this topic, even though Lieu et al's [27] and Popat et al's [28] systematic reviews have been published. Unlike previous systematic reviews, this review provides a higher level of evidence due to the meta-analysis performed.…”
Section: Discussionmentioning
confidence: 95%
“…This was also supported by the research of Malkani et al [9], who performed multivariate Cox regressions, including patient factors and hospital factors. Although a consensus on the infection rate has not yet been reached, most authors have supported that renal transplant patients' infection rate was acceptable and that TJA was a reasonable therapeutic option in those patients [12,28,30,36].…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by the research of Malkani et al (9), who performed multivariate Cox regressions, including patient factors and hospital factors. Although a consensus on the infection rate has not yet been reached, most authors have supported that the infection rate in renal transplant patients was acceptable and that TJA was a reasonable therapeutic option in those patients (12,28,30,36).…”
Section: Discussionmentioning
confidence: 99%
“…Due to inadequate bone stock, most studies have adopted cemented implants, and the results have been satisfactory. Some evidence suggests that cementless implants are also reliable in renal transplant patients (30,40), and Popat et al (28) concluded that cementless implants appeared to be associated with lower failure rates in both hemodialysis patients and renal transplant patients. However, long-term validation for cementless implants is still lacking and heterogeneity in Popat's research is a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent meta-analysis was performed by Popat et al, but this study only included patients who underwent THA. 6 In this study, we performed a comprehensive review assessing the outcome of total knee arthroplasty (TKA) and total hip arthroplasty (THA) in patients who are currently receiving dialysis or have had a KT. Specifically, we reviewed literature published after the year 2000 to answer the following questions: (1) What is the mortality rate after TJA?…”
Section: Introductionmentioning
confidence: 99%